Factors Influences Customer Loyalty for Online Shopping: Study Case on Xiaomi's Online Store Customer in Bekasi - Franky Anggreiawan; Rhian Indradewa (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Customer satisfaction and loyalty are crucial factors for enhancing sales and profitability. In the context of e-commerce, understanding how brand image, product quality, and service quality influence these outcomes is essential for maintaining competitiveness.Purpose: This study investigates the relationship between brand image, product quality, and service quality, and their effect on customer satisfaction and loyalty in the online purchase of Xiaomi products.Design/methodology/approach: A quantitative research approach was employed using Structural Equation Modeling (SEM) to analyze data collected from 105 respondents in Bekasi City who have made at least two transactions through Xiaomi's e-commerce platform. Respondents were selected through simple random sampling, and data were analyzed using SPSS 25 and SmartPLS software.Conclusion: The findings indicate that customer satisfaction mediates the relationship between brand image and customer loyalty. Brand image significantly influences customer loyalty, even without the mediation of customer satisfaction. However, customer satisfaction does not mediate the relationship between product quality and customer loyalty, while service quality directly impacts customer loyalty.Originality/Value (State of art): This study provides insights into the role of brand image and service quality in driving customer loyalty in the e-commerce sector, offering specific recommendations for Xiaomi to implement Standard Operating Procedures (SOPs) to maintain superior product quality and improve service quality for better customer satisfaction and loyalty. Keywords: service quality, product quality, brand image, customer loyalty, customer satisfaction